2020
DOI: 10.1111/jcmm.15067
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TUG1 alleviates cardiac hypertrophy by targeting miR‐34a/DKK1/Wnt‐β‐catenin signalling

Abstract: Cardiac hypertrophy, classified as physiological and pathological hypertrophy, is an adaptive response of the heart to keep normal cardiac function in the condition of pathological injury or abnormal stress. 1 Physiological cardiac hypertrophy, caused by pregnancy or sports training, has normal morphological characteristics and helpful influences on the heart. 2 Pathological cardiac hypertrophy, accompanied by maladaptive cardiac remodelling, altered cardiac morphology as well as abnormal cardiac gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The results demonstrated that CBX2 knockdown elevated P-YAP levels and inhibited YAP expression in the cytoplasm and nucleus, suggesting that CBX2 knockdown promoted YAP translocation, causing the degradation of cytoplasmic YAP. In addition, YAP inhibition suppressed the expression of β-catenin and its downstream signaling molecules, including c-myc and cyclin D1 ( 24 ), which is consistent with the results of the present study. The current study revealed that YAP overexpression reversed the inhibitory effect of CBX2 knockdown on the β-catenin pathway.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results demonstrated that CBX2 knockdown elevated P-YAP levels and inhibited YAP expression in the cytoplasm and nucleus, suggesting that CBX2 knockdown promoted YAP translocation, causing the degradation of cytoplasmic YAP. In addition, YAP inhibition suppressed the expression of β-catenin and its downstream signaling molecules, including c-myc and cyclin D1 ( 24 ), which is consistent with the results of the present study. The current study revealed that YAP overexpression reversed the inhibitory effect of CBX2 knockdown on the β-catenin pathway.…”
Section: Discussionsupporting
confidence: 92%
“…To confirm whether the β-catenin signaling pathway is involved in the role of CBX2 in GC, shRNA-DKK1 was synthesized. As DKK1 is a negative regulator of Wnt/β-catenin signaling ( 24 ), DKK1 was silenced to activate β-catenin signaling. Due to its higher transfection efficiency, shRNA-DKK1-1 was selected for further use, as determined by RT-qPCR ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The lncRNA taurine-up regulated gene 1 (TUG1) was observed during genomic screening in taurine-exposed retinal cells that are much conserved in mammals ( 17 ). Current studies reveal the dynamic expression of TUG1 in the progression and diseases of the heart ( 18 , 19 ). It is, however, not known whether TUG1 may also regulate CME-induced myocardial damage and, if so, what mechanisms are involved.…”
Section: Introductionmentioning
confidence: 99%
“…DKK1 forms a tertiary complex with LRP5/6 and the cell surface co-receptor Kremen-1 with the subsequent internalization of the receptor complex, whereas sclerostin binds to LRP5/6 and prevents binding of Wnt ligands to Frizzled-LRP5/6 receptor complex [81]. Experimental studies indicate that increased DKK1 levels are associated with the alleviation of cardiac hypertrophy [82]. Targeting other parts of Wnt signaling, e.g., Disheveled depletion showed to attenuate left ventricular remodeling [74].…”
Section: Cardiac Hypertrophymentioning
confidence: 99%